HUBUNGAN INTENSITAS KOMUNIKASI KELUARGA DENGAN PRESTASI BELAJAR SISWA KELAS TINGGI SDN 9 TA' KECAMATAN TANETE RIATTANG KABUPATEN BONE - Ertina Ayu; Muh Idris Djafar; Achmad Sabir (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
This research is a type of correlational research that aims to determine whether there is a significant relationship between the intensity of family communication and the learning achievement of high-class students at SDN 9 TA' Tanete Riattang District, Bone Regency. The population in the study were high-class students at SDN 9 TA', Bone Regency, which amounted to 80 students. Then based on the results of inferential statistical analysis, the value = 5.2590 is greater (>) the value = 1.66462 at the 5% significance level. Thus H0 is rejected H1 is accepted. Based on the research, it was concluded that there was a significant relationship between the intensity of family communication and the learning achievement of high-class students at SDN 9 TA', Tanete Riattang District, Bone Regency.